Penerapan Pengelompokan Siswa Berdasarkan Prestasi di Jenjang Sekolah Dasar - Wibowo, Doddy Hendro (Faculty of Psychology, Diponegoro University, 2015)
Students who have high academic grades in school need to be grouped into one class. This paradigm is still inherent in the community and teachers usually use this paradigm to group students who have high academic achievement in the classroom (ability grouping). This research is to provide an overview of the attitudes of teachers, students, and parents with regard to the implementation of ability grouping based on academic achievement. This research is quantitative descriptive study. The study was conducted in one of the public school atÂ Semarang, Central Java, Indonesia, grade IV and V, involving 6 classroom teachers grade IV and Grade V, 166 students and 166 parents. Data was collected using questionnaires and interviews. Result shows, teacher class A (high achievement) agrees, teacher class B (average achievement) and C (low achievement) do not agree with ability grouping. Most students in grade A, B and C agree with ability grouping. Parents of the class A agree, while the parents of the class B and C do not agree with ability grouping.